P545 Antigenic response to CT-P13 and remicade in inflammatory bowel disease patients shows similar epitope recognition. (16th January 2018) - Goncalves, J; Santos, M; Acurcio, R; Iria, I; Gouveia, L; Brito, P; Cunha Santos, A C; Barbas, A; Galvão, J; Barbosa, I; Aires da Silva, F; Alcobia, A; et al.
Abstract: Background: The present study aimed to investigate the cross-reactivity of the CT-P13-reactive sera with Remicade to address the feasibility of therapy switch. To further consolidate the equivalent immunogenicity between the two versions of infliximab we have characterised the epitopes recognised by anti-infliximab antibodies and compared them between CT-P13 and Remicade. Methods: Sera of patients with IBD with measurable anti-CT-P13 antibodies (Remsima or Inflectra) were tested for their cross-reactivity to five batches of Remicade and CT-P13. Sera from patients containing high levels of anti-drug antibodies (>1.0 μg/ml) were used for screening a phage-display library of infliximab peptides and compare antigenic epitopes of anti-CT-P13 and anti-Remicade ADA. Monoclonal antibodies derived from naïve individuals and IBD patients treated with anti-CT-P13 were obtained to gain information on the epitope specificity between anti-CT-P13 and anti-Remicade sera. Results: All 42 anti-CT-P13 and 37 anti-Remicade IBD sera were cross-reactive with Remicade and CT-P13, respectively. ADA concentrations against Remicade or CT-P13 were strongly correlated ( r values between 0.92 and 0.99, p < 0.001 for all experiments, Spearman's correlation test). ADA-negative controls for CT-P13 (5 healthy individuals, 15 patients with RA) were also negative for anti-Remicade. Anti-CT-P13 sera of patients with IBD ( n = 32) exerted similar functional inhibition on CT-P13 or Remicade TNF-α binding capacity and showed reduced binding to CT-P13 in the presence of five different batches of CT-P13 and Remicade. Anti-CT-P13 and anti-Remicade IBD sera selectively enriched phage-peptides from the VH (CDR1 and CDR3) and VL domains (CDR2 and CDR3) of infliximab. Important epitopes were also localised in the constant domain of infliximab heavy-chain (CH1, CH2, and CH3). Sera reactivity detected major infliximab epitopes in these regions to synthetic peptides in 60–79% of patients, and no significant differences were identified between CT-P13 and Remicade ADA. Minor epitopes were localised in framework regions of infliximab with reduced antibody reactivity shown in 30–50% of patients. Monoclonal antibodies derived from naïve individuals and ADA-positive IBD patients treated with CT-P13 provided comparable epitope specificity to five different batches of CT-P13 and Remicade. Conclusions: The present study is the first to compare specific antigenic epitopes between CT-P13 and Remicade, as well as to identify antibody-binding sites on different versions of infliximab with polyclonal and monoclonal IBD sera. The results strongly support a similar antigenic profile for Remicade and CT-P13 and point toward a safe switching between the two drugs in ADA-negative patients.